2021
DOI: 10.35426/iav50n128.05
|View full text |Cite
|
Sign up to set email alerts
|

Obsolescencia del conocimiento financiero

Abstract: El objetivo de este trabajo es describir la relación entre la edad y el conocimiento financiero en México, estimar la tasa de obsolescencia de este entre adultos mayores y explorar cómo el nivel educativo se asocia al mismo. El método de investigación se basa en la aplicación de mínimos cuadrados ordinarios para construir modelos de regresión lineal múltiple y con términos cuadráticos. Los resultados confirman que los adultos mayores experimentan un deterioro significativo en el conocimiento financiero, no nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…On the other hand, in this scientific article, it was evidenced that gender, age, and marital status are significant variables that influence the financial inclusion process, thus contradicting what was obtained by Millán Celis and Jiménez Quitián (2016) , who determined, in their research, gender and age to be non-significant. Regarding age, it was found that the older the person, the greater the probability of financial inclusion; however, this contradicts what was obtained by García-Mata and Briseño-García (2021) , who indicated that older adults as having financial ignorance. In addition, they identified that having a debit card, accruing savings in the last 12 months in a financial institution, and receiving government transfers in the last 12 months allow to expand the possibility of financial inclusion in Colombia.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, in this scientific article, it was evidenced that gender, age, and marital status are significant variables that influence the financial inclusion process, thus contradicting what was obtained by Millán Celis and Jiménez Quitián (2016) , who determined, in their research, gender and age to be non-significant. Regarding age, it was found that the older the person, the greater the probability of financial inclusion; however, this contradicts what was obtained by García-Mata and Briseño-García (2021) , who indicated that older adults as having financial ignorance. In addition, they identified that having a debit card, accruing savings in the last 12 months in a financial institution, and receiving government transfers in the last 12 months allow to expand the possibility of financial inclusion in Colombia.…”
Section: Discussionmentioning
confidence: 56%